An Architecture for Developing Cyber Environments using Multiple HPC Infrastructures for e-Science Applications - Maciel, Felipe; Oliveira, Carina; Juaçaba Neto, Renato; Alencar, João; Rego, Paulo; Bezerra, Ronaldo; Gomes, Danielo; Andrade, Rossana; de Souza, José (Anais do Brazilian e-Science Workshop (BreSci); 2015: Anais do IX Brazilian e-Science Workshop, 2015)
In this paper, we propose a novel architecture to allow the implementation of a cyber environment composed of different High Performance Computing (HPC) infrastructures (i.e., clusters, grids and clouds). To access this cyber environment, scientific researchers do not have to become computer experts. In particular, we assume that scientific researchers provide a description of the problem as an input to the cyber environment and then get their results without being responsible for managing the computational resources. We provide a prototype of the architecture and introduce an evaluation which studies a real workload of scientific applications executions. The results show the advantages of the proposed architecture. Besides, we highlight this work provides guidelines for developing cyber environments focused on e-Science.